Single‐shot phase contrast microscopy using polarisation‐resolved differential phase contrast. Issue 12 (6th September 2021) - Kalita, Ranjan; Flanagan, William; Lightley, Jonathan; Kumar, Sunil; Alexandrov, Yuriy; Garcia, Edwin; Hintze, Mark; Barkoulas, Michalis; Dunsby, Chris; French, Paul M. W.
Abstract: We present a robust, low‐cost single‐shot implementation of differential phase microscopy utilising a polarisation‐sensitive camera to simultaneously acquire four images from which phase contrast images can be calculated. This polarisation‐resolved differential phase contrast (pDPC) microscopy technique can be easily integrated with fluorescence microscopy . Abstract : Phase contrast microscopy provides a label‐free means to visualise structures in transparent samples, including cells and organisms. Implementations with low phototoxicity should enable extended imaging of live subjects that can complement fluorescence microscopy. Building on the development of more quantitative phase microscopy modalities, we present a widely applicable single‐shot phase contrast technique (pDPC) that can provide semi‐quantitative readouts of dynamic samples, which we have applied to Caenorhabditis Elegans .